The relationship between macroeconomic factor and employment growth in Malaysia / Nurazreen Ismail - Ismail, Nurazreen (Faculty of Business and Management, 2018)
Employment growth is a topic that the researcher chooses to study due to the current issue about employment opportunities. Employment growth is a measurement that tracks how many employments are created In the country, In year 2018, there will more job opportunities for Malaysian job seekers as of employers that planning to increase their hiring activity. An increase of 12% compared to year, according to the latest Jobstreet Job Outlook Report for Malaysia. The objective of this study is to know the macroeconomic factor that can affect employment growth in Malaysia. In this study, foreign direct investment. gross domestic product, inflation and urban population growth are important towards employment growth in Malaysia. The researcher used time series data about 34 latest years from 1983 to 2016. The data were analyzed by using pooled ordinary Least Square (OLS) to evaluate the relationship between variables by E-Views 9, from the empirical study, it is shown that the foreign direct investment, gross domestic product, inflation and urban population growth. However. the study further anticipated the addition of supplementary variables to recover the strength and descriptive power of the general model.